2021
DOI: 10.1111/agec.12627
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of global and local value chains to the Covid‐19 pandemic: Survey evidence from vegetable value chains in Senegal

Abstract: In this paper we descriptively investigate the Covid‐19 pandemic's early impact on the fruit and vegetable supply chain in Senegal, using trade statistics and survey data collected through online questionnaires and telephone interviews with smallholder farmers, agro‐industrial companies, agricultural workers, traders, importers, and consumers. Our results point to major differences in how Covid‐19 and containment measures disrupt supply chains between the modern export‐oriented supply chain that is centered ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Those who are increasingly food-insecure, on the contrary, are forced to compromise on the cost and quality of their diet and cut consumption of the most expensive (and healthier) products first [ 108 , 155 , 156 ]. Thus, Hirvonen et al [ 21 ] and Van Hoyweghen et al [ 157 ] revealed that reductions in household food consumption mainly reduced purchases of nutrient-dense foods. Shahzad et al [ 158 ] proved convincingly that households handled the negative income shocks by eating less preferred food and getting support from government and charity organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are increasingly food-insecure, on the contrary, are forced to compromise on the cost and quality of their diet and cut consumption of the most expensive (and healthier) products first [ 108 , 155 , 156 ]. Thus, Hirvonen et al [ 21 ] and Van Hoyweghen et al [ 157 ] revealed that reductions in household food consumption mainly reduced purchases of nutrient-dense foods. Shahzad et al [ 158 ] proved convincingly that households handled the negative income shocks by eating less preferred food and getting support from government and charity organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The literature yielded descriptive studies mostly, showing how Covid-19 affected global agricultural chains and intensified food insecurity worldwide (Tougeron and Hance, 2021). It also triggered a labor shortage in plantations, decreased sales and production, distribution problems, market performance alterations, and increased phytosanitary measures in exports (Van Hoyweghen, Fabry, Feyaerts, Wade, and Maertens, 2021). Therefore, the dichotomous control variable on the impact (YES/NO) of COVID-19 was included because the pandemic could change producers' perceptions about open innovation.…”
Section: Methodsmentioning
confidence: 99%
“…Many low‐ and middle‐income countries have recently suffered a deepening of their balance‐of‐payments constraint on growth and a fall in both international remittances and wage employment opportunities, especially in domestic wage employment opportunities for the least skilled and poorest (Kalantaryan and McMahon, 2020; Wageningen University and Research, 2020). When low‐income African economies began to be disrupted by COVID‐19, the larger, vertically integrated enterprises in the fresh fruit and vegetables (FFV) export supply chains demonstrated much more resilience and innovation than most of the small producers and traders in the domestic FFV chains (Van Hoyweghen et al., 2021). Designing effective policies on the basis of country‐specific constraints on export expansion is becoming increasingly important as, in the wake of COVID‐19, the high‐value agricultural export products on which we focus may offer a lifeline to large numbers of people seeking seasonal and permanent rural wage employment.…”
Section: The Need To Refresh Debates On Structural Changementioning
confidence: 99%